Efforts To Increase The Effect Of The Disciplinary Development Program In The Teaching And Learning Process On The Independent Work Ethic Of Teachers At SD Negeri 026 Rambah, Rambah District, Rokan Hulu Regency - Nuraisah Nuraisah (Indonesian Journal of Basic Education, 2022)
This research is an effort to increase the effectiveness of the disciplinary development program in the teaching and learning process towards the independent work ethic of teachers at the 026 public elementary school in Rambah, Rambah sub-district, Rokan Hulu district. From this study it can be concluded that the implementation of inspections and official visits by educational supervision is very helpful for teachers at the 026 Rambah State Elementary School, Rambah District, Rokan Hulu Regency, Riau Province to further improve self-quality and self-performance management from a sense of discipline that is implemented into the process. bemlamjmamr teaches in class